2020
DOI: 10.1186/s43055-020-00217-y
|View full text |Cite
|
Sign up to set email alerts
|

Intermodality agreement between TTE and low kVp ECG-gated MDCTA in diagnosis of complex CHD in pediatrics

Abstract: Background Transthoracic echocardiography (TTE) is considered the primary diagnostic modality in congenital heart disease (CHD). However, it has limited role in evaluation of extra-cardiac major vessels abnormalities. Cardiac catheterization angiography is considered the gold standard investigation, yet, it is invasive. The aim of this study is to evaluate the agreement between TTE and low kVp ECG-gated cardiac multi-detector CT angiography (MDCTA) in detecting cardiac and extra-cardiac findings of complex con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…Our study showed moderate agreement between MDCT and Echocardiography in diagnosis of left sided SVC (Kappa =0.435, P =0.004, with AUC of 0.976). This was close to Abdullah et al (17) and Ali et al (10) who showed that MDCT was superior to TTE in diagnosing SVC anomalies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study showed moderate agreement between MDCT and Echocardiography in diagnosis of left sided SVC (Kappa =0.435, P =0.004, with AUC of 0.976). This was close to Abdullah et al (17) and Ali et al (10) who showed that MDCT was superior to TTE in diagnosing SVC anomalies.…”
Section: Discussionsupporting
confidence: 90%
“…908, P <0.001) with area under the curve was 0.898. Ali et al (1) and Ali et al (10) agreed with the current study, and they stated that there was very good agreement between MDCT and Echo in detecting ASD, VSD, and combined ASD and VSD where k 0.851. However, Saad et al (11) demonstrated that Echo was more effective than MDCT at detecting ASD, ASD, and septal aneurysms.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the pulmonary artery branches (RPA and LPA), Chi square test revealed a statistically significant difference between both ECHO and MSCT in their assessment (p=0.008). This came in agreement with Liu et al, (2016) [21] and Ali et al, (2020) [22] who declared that MDCT was much informative than ECHO which missed the diagnosis of pulmonary artery anomalies and other extracardiac vascular anomalies due to limited acoustic windows, low spatial resolution and structures are obscured by overlying bone and aerated lung.…”
Section: Discussionsupporting
confidence: 85%